The Effectiveness 0f Employee Performance in Marriage Registration Services at the Religious Affairs Office of Pare District, Kediri Regency - Allya Almuqrhoina Fajri; Agus Widiyarta (Jurnal Impresi Indonesia, 2024)
The most important thing to monitor in registering marriages to the public is employee performance which will later become an indicator of the organization's success in carrying out its duties and obligations. This research aims to determine the effectiveness of employee performance in marriage registration services at the Religious Affairs Office of Pare District, Kediri Regency. This research uses a qualitative approach. Data collection techniques use interview, observation and documentation techniques which are linked to the theory of employee performance effectiveness according to Admosoeprapto (2016). The results of the research show that the performance of the employees of the Religious Affairs Office of Pare District, Kediri Regency can be said to be effective in meeting the needs of the community in marriage registration services. However, the Religious Affairs Office of Pare District, Kediri Regency, in terms of quantity of work, needs to increase the number of employees to make it easier for employees to serve the large number of marriage registration requests from the public every year.